2021
DOI: 10.3390/nu13124345
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in Food Allergy and Immunomodulation

Abstract: Food allergy (FA) is an increasing problem worldwide and, over recent years, its prevalence is rising in developed countries. Nowadays, the immunological and cellular processes that occur in the allergic reactions are not fully understood, which hampers the development of in vitro diagnostic tools and further treatment options. Moreover, allergic diseases could be reinforced by environmental exposure and genetic modifications. Gene expression can be controlled by different epigenetic mechanisms like DNA methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…Today, it has been proven that the long arm of the fifth chromosome regulates cytokine genes involved in the allergic process, namely IL-4, IL-5, IL-6, IL-9, IL-12, and IL-13 [ 8 ]. Cytokines are important mediators of intercellular interactions that regulate the immune response as well as the cell cycle, and are involved in numerous physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, it has been proven that the long arm of the fifth chromosome regulates cytokine genes involved in the allergic process, namely IL-4, IL-5, IL-6, IL-9, IL-12, and IL-13 [ 8 ]. Cytokines are important mediators of intercellular interactions that regulate the immune response as well as the cell cycle, and are involved in numerous physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics is considered to be one of the most promising areas of research for understanding the development of food allergies [ 7 ]. Understanding the epigenetic components that may underlie food allergies opens new perspectives because epigenetic components are reversible and can be modified or eliminated if necessary, in contrast to purely genetic components [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a pilot study on patients allergic to grass pollen and house dust mites treated with dual sublingual immunotherapy suggested that such treatment could be effective and that long-term tolerance to the allergens administered by AIT could be induced by epigenetic modifications of Foxp3 in memory regulatory T cells [ 19 ]. Another recent investigation found that in food allergy, epigenetic mechanisms, as well as reducing genetic modifications, can also produce modifications in immune genes, influencing, for example, immunomodulation and possibly explaining the sustained responsiveness or unresponsiveness during immunotherapy triggered by epigenetic modifications in key genes that induce tolerance of a number of foods [ 20 ].…”
Section: Omicsmentioning
confidence: 99%
“…Furthermore, Th1 and Th2 cell differentiation and cytokines production (IL-4, -6, -13, TNF-α) in these cells can be controlled using various cellular transcription factors (GATA-3, T-bet) [1][2][3]. According to Yates et al, Cañas et al, and Gandihi et al, Th1 and Th2 responses have been applied to in vivo studies, and Th1/Th2 reagents and extracts have been developed [4][5][6]. Anti-inflammatory drugs, antihistamines, or anti-leukotriene drugs are prescribed and used as therapeutic agents for inflammatory and allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a mouse allergy model (ovalbumin (OVA)-sensitized BALB/c mice) was used to examine the anti-allergic activities of ZLE or tricin. have been applied to in vivo studies, and Th1/Th2 reagents and extracts have been developed [4][5][6]. Anti-inflammatory drugs, antihistamines, or anti-leukotriene drugs are prescribed and used as therapeutic agents for inflammatory and allergic diseases.…”
Section: Introductionmentioning
confidence: 99%